Students’ satisfaction towards service quality at UiTM Melaka City Campus’s Library / Nur Shazwani Mohamad Kamal and Syahida Azwa Md Said - Mohamad Kamal, Nur Shazwani; Md Said, Syahida Azwa (Faculty of Administrative Science and Policy Studies, 2014)
This study examines the the factors that influences students satisfaction towards service quality at UiTM Melaka City Campus’s library. Reviews of the literature show that there few factors that influenced the students satisfaction towards service quality. Studies done by other reserachers were used as guidelines to determine what factors that can be tested in this study, and the factors are regarding on SERVQUAL dimension (tangible, realiability, responsiveness, assurance and empathy). A questionnare survey was distributed to 357 respondents among students UiTM Melaka City Campus that get service at library. A total of 357 valid responses were obtained. Data analysis shows that significant relationship exists between five factors towards students satisfaction towards service quality at UiTM Melaka City Campus’s library. Assurance emerged as the most influential factors that influences students satisfaction towards service quality at UiTM Melaka City Campus’s library.